Perfil competitivo como herramienta para la gestión estratégica de la investigación en universidades (2020)
To manage strategically is to achieve a competitive advantage and to maintain it. For this purpose, the competitive profile matrix (CPM), based on the key success factors (KSF), allows to position oneself against competitors. In this sense, the aim of this reflection is to propose a management tool to guide the development of competitive advantages in research at universities, taking into account the KSF identified in previous research (researchers, resources, visibility and development model). Information is collected through theoretical review by experts in strategic planning, and processed through content analysis and hermeneutics. The study reveals that the application of a CPM would serve for each institution to develop its competitive profile, and based on this, design a strategic plan —in order that it strengthens the KSFs in which it has leadership and develops those that require greater resources. Including this tool in the strategic planning of academic institutions would make it possible to guide them permanently towards success, since it could lead to allocating resources to the key factors that will ensure their objectives of regional leadership in research and global visibility. In addition, they could adopt the best practices of that university or universities that surpass them in a certain factor.